Training in Pediatric Surgical Oncology - Losty, Paul D. (Frontiers in Pediatrics, 2022)
Paediatric Surgical Oncology is a challenging sub-speciality field requiring strong discipline , resilience and a “ never quit “ attitude. Paediatric cancer patients are frail, vulnerable and have life limiting illness were the skill(s) of the operating surgeon may determine ‘ cure ‘ and survival or untimely death from inadequate tumour resection with disease progression and / or ‘ never event ‘ misadventure. It could be stated therefore that a career in surgical oncology may not be for the ‘ faint hearted ‘ surgeon. Training in a high volume centre(s) accredited in the delivery of high quality care and clinical excellence driven by inspirational leaders in surgical oncology with motivated multidisciplinary teams is key. International surgery oncology fellowship(s) add significant credits to a residents’ clinical training crucially also yielding opportunities for gaining research skills. On the journey towards subspeciality accreditation the aspiring surgeon oncologist must first demonstrate skill set(s) proficiency in general paediatric surgery residency training to advance to the next phase(s). This article offers a ‘ snap shot ‘ overview synopsis of paediatric surgical oncology training in its broadest perspective(s) for those seeking further information and career guidance.